2013
DOI: 10.4103/0975-1475.119780
|View full text |Cite
|
Sign up to set email alerts
|

Gender determination using cheiloscopy

Abstract: Background:Although lip prints have been used as an evidence for human identification in forensic science, there exists a doubt about its role in gender determination.Aims:The present study was designed for documenting common patterns, as well as their variation in the study population, with objective of evaluating uniqueness of the lip print pattern among the study population, as well as to evaluate the possibility of gender determination.Study Design:Two hundred and thirty five lip prints were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…in their study. [ 12 ] They observed that reticular and dotted patterns were commonly found in the upper lip of males and complex pattern in the upper lip of females. Gondivkar SM et al .…”
Section: Resultsmentioning
confidence: 99%
“…in their study. [ 12 ] They observed that reticular and dotted patterns were commonly found in the upper lip of males and complex pattern in the upper lip of females. Gondivkar SM et al .…”
Section: Resultsmentioning
confidence: 99%
“…In domain 1, almost all studies achieved a low risk of bias, and only one article was classified as high risk [ 25 ]. Regarding the characterization of the population, 10 studies failed to present the necessary data, and, within these, one article did not specify the distribution of participants by sex [ 26 ], leading to a high risk of bias. Still, most of the articles (31/41) specify all the population statistics.…”
Section: Resultsmentioning
confidence: 99%
“…The studies were published between 1982 and 2019, and were from India (n = 52) 1 , 4 – 6 , 10 – 15 , 25 , 27 , 30 , 31 , 35 40 , 43 – 46 , 48 50 , 53 – 57 , 59 – 62 , 64 , 66 – 75 , 78 , 79 , 81 , 83 , 84 , Egypt (n = 3) 2 , 42 , 58 , Brazil (n = 3) 26 , 34 , 76 , Portugal (n = 2) 32 , 51 , Pakistan (n = 2) 47 , 77 , Colombia (n = 2) 29 , 52 , Nepal (n = 2) 33 , 82 , France (n = 1) 24 , Iran (n = 1) 63 , Romania (n = 1) 41 , Croatia (n = 1) 65 , Saudi Arabia (n = 1) 28 and Poland (n = 1) 80 . The total sample of participants across studies was 22,965.…”
Section: Resultsmentioning
confidence: 99%
“…Fifty eligible studies 2 , 4 , 5 , 10 , 14 , 25 , 26 , 28 30 , 32 , 35 , 38 40 , 42 , 44 – 46 , 49 – 58 , 60 63 , 66 – 72 , 74 , 76 79 , 81 84 had low risk of bias, while 22 studies 1 , 6 , 11 – 13 , 15 , 24 , 27 , 31 , 33 , 36 , 37 , 41 , 43 , 47 , 48 , 59 , 64 , 65 , 73 , 75 , 80 had moderate risk of bias (Tables 3 and 4 ). All the questions in JBI tool for cross-sectional studies were applicable, while three questions were not applicable in the JBI tool for diagnostic test accuracy studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation